2020
DOI: 10.21873/invivo.12014
|View full text |Cite
|
Sign up to set email alerts
|

Taller-than-wide Thyroid Nodules With Microcalcifications Are at High Risk of Malignancy

Abstract: Background/aim: Previous studies have shown that there may be a diversity in the ultrasonographic (US) features discriminating a malignant from a benign thyroid nodule. We determined the reliability of the specific nodule shape in combination with other US features in predicting thyroid carcinomas. Patients and Methods: This was a retrospective single-center study investigating the association of the morphological characteristics of nodular goiters from preoperative US and color Doppler images with malignancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The taller-than-wide shape (vertical) was significantly associated with malignancy [23]. Taller-than-wide nodules with microcalcifications were most likely to be malignant, and there was a strong negative correlation between the size and taller-than-wide shape of a thyroid nodule [24]. Those with a nodule size between 30 and 59 mm had a 26% greater malignancy risk than those with nodules <30 mm in largest diameter [25].…”
Section: Discussionmentioning
confidence: 98%
“…The taller-than-wide shape (vertical) was significantly associated with malignancy [23]. Taller-than-wide nodules with microcalcifications were most likely to be malignant, and there was a strong negative correlation between the size and taller-than-wide shape of a thyroid nodule [24]. Those with a nodule size between 30 and 59 mm had a 26% greater malignancy risk than those with nodules <30 mm in largest diameter [25].…”
Section: Discussionmentioning
confidence: 98%
“…Microcalcification was also included as a predictor in the model. Previous studies have reported that microcalcification is closely related to PTC based on coloured Doppler images combined with contrast-enhanced ultrasonography (CEUS), showing that microcalcification is a strong predictor for PTC [ 39 , 40 ]. However, various scholars have also proposed that CEUS has difficulty in determining whether the tiny hyperechoic foci derived from microcalcifications or colloid crystals sometimes lead to biases in predictions of the model, thus requiring constant observation in subsequent work [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler can confirm the presence of calcification (P<0.05). Data in some studies (31)(32)(33) indicates that microcalcification has high specificity (95%) and low sensitivity (29-36%) for malignant thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%